Analisis Peran Auditor Internal Pemerintah dalam Mitigasi Risiko Fraud pada Sektor Pemerintahan - Sri Wulandari; Arsyadona Arsyadona (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Fraud in the government sector is a serious issue that can threaten the stability and efficiency of governance. This study aims to analyze the role of internal government auditors in mitigating fraud risk. The method used is a literature review with a qualitative descriptive approach, examining 10 relevant journals. The results indicate that internal auditors play a crucial role in detecting and preventing fraud by thoroughly examining internal control weaknesses and utilizing modern technology such as Whistleblowing Systems. The effectiveness of internal audits is supported by strong leadership and high awareness of fraud risks, as well as appropriate structural reform policies. The study concludes that effective internal auditing is essential in enhancing transparency and accountability and recommends the need for comparative analysis across regions to evaluate the diversity of internal audit practices. Additionally, further research is needed to explore the impact of information technology and Whistleblowing Systems in fraud prevention, as well as the role of leadership and organizational culture in supporting the internal audit function.